Antibacterial Effectiveness of Syzygium cumini (L.) Skeels Leaves to Escherichia coli pBR322 - Mere, Janrigo Klaumegio; Bintang, Maria; Safithri, Mega (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2021)
Bacterial resistance is a serious problem that until now still has become a global problem. The search for new antibacterial compounds is needed to overcome this problem. Syzygium cumini (L.) Skeels is a plant known to contain bioactive compounds that can be used as an antibacterial agent. This study aims to explore the leaves of this plant as an antibacterial against Escherichia coli pBR322 resistant bacteria. Based on the antibacterial test results, extracts and leaf fractions of this plant can inhibit bacterial growth. Ethyl acetate fraction at a concentration of 800 ppm showed strong antibacterial activity with an inhibition zone diameter of 10.36±0.02 mm followed by ethanol extract and other fractions, namely 8.43±0.01 mm (ethanol extract), 7.24±0.01 mm (water fraction), and 1.45±0.01 mm (n-hexane fraction). The results of spectrophotometric MIC determination also showed inhibition against bacterial growth, which was marked by a decrease in the absorbance value at the lowest antibacterial concentration of 600 ppm from 0.454 to 0.070 at wavenumber 600 nm after 24 hours of incubation. The decrease in the absorbance value indicated that the antibacterial properties of the plant leaves at this concentration were effective in inhibiting bacterial growth.